Multidisciplinary Approach to Evaluation of Forensic Psychiatry Reports - Aydın, Sare; Batmaz, Sedat; Akpınar Aslan, Esma; Çelikbaş, Zekiye; Çetin, Selçuk (The Bulletin of Legal Medicine, 2021)
Objective: We aimed to determine the content of forensic psychiatric reports prepared in a university hospital, which institutions requestedreports, which report was requested based on which law article, which branches of medicine were cooperated with; to raise awareness about frequently encountered forensic psychiatric cases by psychiatrists and psychiatry residents; and to emphasize the need for continuous and up- to-date training in this field.Methods: Descriptive statistical analyses were conducted using the data in the hospital electronic records of 272 participants aged 18 years and over, for whom preparation of a forensic psychiatric report was requested.Results: Considering the psychiatric diagnoses of the cases, 69 (25.4%) were not diagnosed with any mental disorder, 59 (21.9%) with mental retardation, 33 (12.1%) with psychotic disorders, and 29 (10.6%) with dementia. The majority of the distribution of the reasons for requesting a report was about whether there was criminal responsibility (31.3%), whether there was need for guardianship (27.9%), and whether the victim could defend themselves (14.0%). 39.3% of the requests came from courts, 30.2% from prosecutors and 20.6% from law enforcement officers. No law was specified for 187 of the cases (68.8%). More than half of the cases (53.6%) were consulted from neurology.Conclusion: The results of the study showed the reasons for report requests frequently encountered in psychiatry practice, different authorities that these requests came from, distribution of frequent psychiatric diagnoses and other departments that were consulted together with psychiatry. Giving priority to training covering these areas will meet the needs of...
Keywords: Forensic psychiatry; Criminal responsibility; Guardianship